Matter of Articles 859-864 of ABGB in Serbian Civil Code and in Positive Serbian Law With Respect to the Reception of Roman Law - Kulauzov, Maša; Milutin, Milan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The aim of the research in this phase is reflected, on the one hand, in the effort to determine possible nominal similarities and differences in the way in which the three acts regulate the issues contained in Articles 859-864 of ABGB, i.e. the legal basis of obligations, public promise of reward, conclusion of a contract, division of a contract and other related issues. The research should serve as a starting point for a detailed comparative analysis of each of the above issues in future works. On the other hand, the secondary aim is to make a comparison with the corresponding rules of Roman law, where possible, in the context of finding possible results of reception. The paper applies linguistic interpretation of the sources, after which they are analysed using the dogmatic method. After establishing the meaning of the norm, its logical nature and elements are discussed, as well as relations with other legal rules, using the normative method, and – in the context of different historical circumstances and legal systems in which they were enacted – historical law- and comparative law methods. The similarities and differences in the Austrian and the two Serbian acts are the result of both the level of development of the societies at the time the acts were adopted, their needs at the time, challenges in legal practice, but probably also the personal pedantry and systematicity of the authors.